Analysis of Strategy for Development of Halal Tourism Potentials in Syariah Hotels in West Java - Usep Deden Suherman (Li Falah: Jurnal Studi Ekonomi dan Bisnis Islam, 2018)
Halal tourism potential in West Java, especially for sharia hotels is very high so that West Java is a potential area for developing halal tourism. To realize West Java as a halal tourism development area is not easy there are obstacles faced such as the lack of consumer interest in sharia hotels and not many people understand the difference between sharia hotels and conventional hotels. Therefore, this study will examine the development strategy of halal tourism in West Java.The purpose of this study is 1) to identify internal factors (strengths and weaknesses) in the development of sharia tourism in West Java, 2) to identify external factors (opportunities and threats) in the development of sharia tourism in West Java, 3) for knowing the positioning of West Java in the development of sharia tourism and 4) to find out the development strategy of sharia tourism in West Java.The research method used is qualitative descriptive. The study was conducted on 8sharia hotels in the West Java region. The data analysis technique used is SWOT analysis using internal factors and external factors of the company.The SWOT matrix calculation results produce ten alternative strategies, namelyencouraging and providing halal certification facilities for sharia hotels, conductingassessment of facilities and infrastructure, halal tourism needs and other supportingelements in West Java, increasing the promotion of sharia tourism through various mediaand providing tourism information based on information technology that suits the needs of tourists, conducts an inventory of data in collaboration with the city or district government to hotels that implement the concept of sharia in West Java, develop uniqueness as excellence found in sharia hotels in West Java, Cooperate with various parties including the tourism ministry, the community and other stakeholders, equating the perception of the concept of sharia tourism between the government and business actors through halal tourism discussions and seminars, Developing various tourism products Halal with the aim of attracting tourists, conducting training and coaching Islamic tourism HR in accordance with the standards of the MUI, providing a place of worship complete with other worship facilities and infrastructure. The results of this study are expected to be a recommendation to the government of West Java Province and sharia hotels in the development of halal tourism in West Java.